2021
DOI: 10.1088/1361-6501/ac0844
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive diagnosis of grounding grids based on the electromagnetic induction impedance method

Abstract: When attempting to detect faults in grounding grids, the electromagnetic induction method is hampered by the failure of fault diagnosis based on magnetic flux density detection. An electromagnetic induction impedance method is proposed to diagnose corrosion faults by detecting the induced impedance. A non-destructive testing prototype was developed. The sensor of the prototype consists of biaxial sensing coils, a frequency selection module, and a dual-channel synchronous demodulator. The biaxial sensing coils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…As a method for classroom behaviour monitoring, open-pose bone detection has also been suggested. According to aerobics teaching practise, it is critical and superior to employ an ideological and political education teaching style that emphasises “autonomy-cooperation-exploration” in courses [ 32 ]. A new approach to improving the ability of aerobics training to convey political and ideological education was sought by these academics.…”
Section: Introductionmentioning
confidence: 99%
“…As a method for classroom behaviour monitoring, open-pose bone detection has also been suggested. According to aerobics teaching practise, it is critical and superior to employ an ideological and political education teaching style that emphasises “autonomy-cooperation-exploration” in courses [ 32 ]. A new approach to improving the ability of aerobics training to convey political and ideological education was sought by these academics.…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, only 60% of teachers' normal use of new media was examined, and the methods of enhancing media literacy education are investigated from three aspects: social factors, media factors, and students' factors. The authors in [15] integrated the short video recommendation model with the features of new media to recommend innovative ideas for ideological and political work in colleges. Ford and Jennings [16] employed the Western European political profile and discussed the critical problems in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the booming DL technology has gradually been applied to study the behavior, state, and fatigue of students in classrooms (Stoeve et al, 2021). For example, Melkonian et al (2017) and Song et al (2021) found that the concentration degree of students in the classroom could be evaluated by profile face detection algorithms, changes in eye closure, and head-up and head-down behavior recognition. Hu and Zhang (2021) proposed an eye and nose detection method using a facial recognition model based on DL to evaluate the attention of the students in the classroom.…”
Section: Teaching Techniques Of Ideological and Political Courses In Colleges And Universitiesmentioning
confidence: 99%